Intramyometrial and intravenous oxytocin compared to intravenous carbetocin for prevention of postpartum hemorrhage in elective cesarean section—A quasi‐randomized controlled phase IV non‐inferiority interventional trial - Romana Brun; Lea Meier; Elisabeth Kapfhammer; Roland Zimmermann; Nicole Ochsenbein‐Kölble; Christian Haslinger (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Our objective was to assess non‐inferiority of the unique approach used in our institution of combined 10 IU IM (intramyometrial) and 10 IU IV (intravenous) oxytocin to carbetocin IV in preventing severe postpartum blood loss in elective cesarean sections. The design was a prospective controlled phase IV non‐inferiority interventional trial. The setting was a tertiary center at University Hospital, Zurich, Switzerland. Material and Methods The population consisted of 550 women undergoing elective cesarean section after 36 completed weeks of gestation at low risk for postpartum hemorrhage (PPH). Participants were assigned to either combined oxytocin regimen (10 IU IM and 10 IU IV) or carbetocin (100 μg IV). Non‐inferiority for oxytocin for severe PPH was assessed with a 0.05 margin using the Newcombe–Wilson score method. The main outcome measures were severe postpartum blood loss defined as delta hemoglobin (∆Hb, Hb prepartum—Hb postpartum) ≥30 g/L. Results Non‐inferiority of combined oxytocin (IM/IV) in preventing severe postpartum blood loss was not shown (17 women in the oxytocin group vs. 7 in the carbetocin group). The number needed to treat when using carbetocin was 28. The risk difference for ∆Hb ≥30 g/L was 0.04 (oxytocin 0.06 vs. 0.03), 95% confidence interval (CI) (0.00–0.08). No significant difference was observed for ∆Hb (median 12 [IQR 7.0–19.0] vs. 11 [5.0–17.0], p = 0.07), estimated blood loss (median 500 [IQR 400–600] vs. 500 [400–575], p = 0.38), or the PPH rate defined as estimated blood loss ≥1000 mL (12[4.5] vs. 5 [2.0], risk difference 0.03, 95% CI (−0.01 to 0.06), p = 0.16). More additional uterotonics were administered in the oxytocin group compared to the carbetocin group (15.2% vs. 5.9%, p = 0.001). Total case costs were non‐significantly different in the oxytocin group (US $ 10 146 vs. 9621, mean difference 471.4, CI (−476.5 to 1419.3), p = 0.33). Conclusions Combined (IM/IV) oxytocin is not non‐inferior to carbetocin regarding severe postpartum blood loss defined as postpartum Hb decrease ≥30 g/L in elective cesarean sections. We recommend carbetocin for use in clinical practice for elective cesarean sections.